2021
DOI: 10.1097/jcp.0000000000001404
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3, Placebo-Controlled Trial of Once-Daily Viloxazine Extended-Release Capsules in Adolescents With Attention-Deficit/Hyperactivity Disorder

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 55 publications
2
71
0
Order By: Relevance
“…The average effects of viloxazine ER on EFDs appeared to be clinically relevant as a substantial proportion of subjects had significant improvements in EFDs. This work extends the previous findings [ 18 21 ] of viloxazine ER demonstrating improved ADHD symptoms, and may have implications for clinicians when planning treatment of children and adolescents with ADHD and EFD.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The average effects of viloxazine ER on EFDs appeared to be clinically relevant as a substantial proportion of subjects had significant improvements in EFDs. This work extends the previous findings [ 18 21 ] of viloxazine ER demonstrating improved ADHD symptoms, and may have implications for clinicians when planning treatment of children and adolescents with ADHD and EFD.…”
Section: Discussionsupporting
confidence: 84%
“…We used data from four double-blind, three-arm, parallel-group, placebo-controlled, phase III clinical trials of viloxazine ER in children and adolescents (6–17 years of age) with ADHD (Table 1 ) [ 18 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A novel extended‐release version of viloxazine, SPN‐812, has recently been approved by the U.S. Food and Drug Administration as a nonstimulant treatment for attention deficit/hyperactivity disorder (ADHD) in children and adolescents. 2 , 3 , 4 , 5 , 6 Recent in vitro and in vivo animal studies have elucidated a multimodal mechanism of action, with demonstrated activity on norepinephrine and serotonin. 7 …”
mentioning
confidence: 99%